Short‐term impacts of COVID‐19 on family caregivers: Emotion regulation, coping, and mental health. Issue 2 (31st July 2021) - Russell, Beth S.; Hutchison, Morica; Park, Crystal L.; Fendrich, Michael; Finkelstein‐Fox, Lucy
Abstract: Background: The negative mental health impact of coronavirus disease 2019‐related stressors may be heightened for those caring for children, who bear responsibity for their welfare during disasters. Aim: Based on the Transactional Model of Stress and Coping, we inquired whether caregivers' emotion regulation and coping behavior were associated with posttraumatic stress symptoms (PTSS). Materials & Methods: Data were collected through a national online survey in April 2020, and again 60 days later. Results: Of the 801 longitudinal cases, 176 (63.6% female; mean age = 33.5) reported caring for minors in their homes during the pandemic. Over 20% of caregivers experienced clinically concerning PTSS, rates higher than their noncaregiving counterparts. Regression analysis indicates caregivers' baseline mental health symptoms and emotion regulation predicted PTSS 60 days later. Discussion: Implications for needed parenting supports among families experiencing traumatic stress are provided. Conclusion: Anxiety symptoms at baseline were the most significant and consistent contributor to all models and were significantly higher among those with clinically concerning levels of PTSS suggesting a clear intervention target.